Multi-omics analysis of Populus simonii × P. nigra leaves under Hyphantria cunea stress - Jiang, Jiahui; Fan, Gaofeng; Wang, Ruiqi; Yao, Wenjing; Zhou, Boru; Jiang, Tingbo (Frontiers in Plant Science, 2024)
Poplar is an important greening and timber tree species in China, which has great economic and ecological values. However, the spread of Hyphantria cunea has become increasingly serious in recent years, resulting in huge economic loss of poplar production. Exploring the molecular mechanism of stress incited by H. cunea on poplar has significant implications for future development of new insect-resistant poplar varieties using genetic engineering technology. In this study, a total of 1039 differentially expressed genes (DEGs), 106 differentially expressed proteins (DEPs) and 212 differentially expressed metabolites (DEMs) were screened from Populus simonii × P. nigra leaves under H. cunea stress by transcriptome, proteomics and metabolomics analysis, respectively. GO and KEGG analysis showed that the DEGs and DEPs are associated with endopeptidase inhibitor activity, stress response, α-linolenic acid metabolism, phenylpropanoid biosynthesis and metabolic pathways, cysteine and methionine metabolism pathways and MAKP signaling pathway. Metabolomics analysis showed the most of DEMs were lipids and lipid molecules and the pathways associated with transcriptome mainly include plant hormone signal transduction, α-linolenic acid metabolic pathway, amino sugar and nucleotide sugar metabolism, and phenylpropanoid biosynthesis. In particular, multi-omics analysis showed that several pathways such as α-linolenic acid metabolic, phenylpropanoid biosynthesis and metabolic pathway and cysteine and methionine metabolic pathway were significantly enriched in the three omics, which may play an important role in the resistance to pests in poplar.